Strengthening Resilience through Reflective Writing based on Surah Al-Fatihah - Rinova Cahyandari; Ahmad Miftahul Ghina; Arif Agustiyan (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Mental health is one dimension of an individual's health in living life. Various life challenges have the potential to create tension and can lead to psychological distress. Including college students who have various role conflicts have their own challenges in being able to achieve balance in their daily lives. One individual concept that supports a healthy mental state is resilience. The aim of this research is to determine the extent to which psychotherapy in the form of reflective writing through Surah Al-Fatihah is able to have an impact on increasing resilience in college student respondents. Data was obtained through a Resilience questionnaire which had been tested for validity and reliability. This research is quantitative research involving 56 college student respondents. The results of statistical tests show that psychotherapy in the form of reflective writing through the surah Al-Fatihah can increase resilience. Al-Fatihah is able to strengthen resilience because it contains the concept of tauhid so that it teaches more deeply about Allah SWT and the human relationship as a servant of Allah in carrying out various aspects of life.